From the Paddock to the Page: Squatter Peter Beveridge's Ethnological Writing about the Wadi Wadi in Colonial Victoria. Issue 3 (27th October 2016) - Lourie, Amanda
Abstract : This article examines the ethnological writing about the Wadi Wadi people undertaken by squatter Peter Beveridge in the 1850s and 1860s. In the north of the colony of Victoria, both Beveridge and the Wadi Wadi laid claim to the land upon which they lived. In this ambiguous space, lengthy and close relationships developed between Beveridge and Wadi Wadi people with information and experiences shared. Valuing the knowledge of Wadi Wadi people, Beveridge was able to adapt and challenge aspects of the British ethnological ideas through which he framed his analysis of Wadi Wadi life. The article explores specifically Beveridge's response to the 1841 Queries Respecting the Human Race . It appears that Beveridge purposefully ignored the questions on Physical Characters and recognised spiritual belief as an integral part of Wadi Wadi daily life.